Owl and Penguin - Madan, Vikram (New York : Holiday House, 2022)
Despite their differences, two unlikely friends flock together like birds of a feather.
Ice cream -- Flying -- Splish-splash.
Keywords: Owls -- Comic books, strips, etc; Penguins -- Comic books, strips, etc; Friendship -- Comic books, strips, etc; Owls -- Fiction; Penguins -- Fiction; Friendship -- Fiction; Cartoons and comics; Graphic novels; Animal fiction